Weavers’ Aesthetic Perception on the Visual Complexity of Pua Kumbu Design Motifs : An Exploratory Study - Wan Juliana, Emeih Wahed; Noorhayati, Saad; Saiful Bahari, Hj Mohd Yusoff; Patricia Pawa, Pitil (2021)
Visual complexity can offer a unique direction on how perceivers react and shape their aesthetic perceptions, relying on the art’s formalistic elements and visual content. This study aims to evaluate the weavers’ aesthetic perception of the complexity of the Pua Kumbu design motifs. The complicated art piece was highlighted as the Iban identity, which resembles the Iban’s way of life, beliefs, taboos, and surroundings hidden in the textile patterns. The weaver’s interpretation is its success in transferring the knowledge to the perceivers as they are the storyteller of this majestic art piece. The complexity of the symbols presented in the design motifs contributes to the lack of interest, especially among the young generation, in understanding these motifs' meaning. Thus, a qualitative approach was used to explore the weavers’ perception of the design motifs’ complexity using interviews in structured and unstructured questions. The findings contributed to a basic understanding and the sustainability of traditional human values, hoping that the textile as a valuable heritage will survive and remain relevant for the long term.